Addressing the needs and identifying supports for parents of chronically ill adolescents and young adults in their shared transition from paediatric to adult care: a scoping review protocol - Kate Murray; Karen Frost; Samantha K Micsinszki; Pranshu Maini; Claudia Tersigni; Sarah Cairns (BMJ Open, 2025)
Introduction The transition from paediatric to adult healthcare marks a pivotal period for chronically ill adolescents, as they transition from a highly supportive and family-oriented environment to an adult-oriented and a more individual-oriented healthcare system that places a greater emphasis on personal responsibility and independence. Parents, given their firsthand experience managing their child’s healthcare, play a central role in ensuring a smooth and successful transition, yet their perspectives on the barriers and facilitators of this complex process remain vastly underexplored. This scoping review aims to assess and provide comprehensive insights into parents’ perceptions of the successes and challenges during their adolescents’ transition from paediatric to adult healthcare.Methods and analysis This scoping review is led by patient partners and will be guided by the Peters et al and the Joanna Briggs Institute guidelines for scoping reviews. The preliminary search strategy will be developed and calibrated in Ovid MEDLINE and will be subsequently replicated in the Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsychInfo, Embase, Web of Science and Sociological Abstracts from inception through 18 December 2024, including all types of studies. Grey literature sources recommended by patient partners and clinical and qualitative research experts will also be included. Two reviewers will independently perform the title and abstract review of all studies against the predefined inclusion and exclusion criteria, followed by the full-text review of included studies. The reference list of all included studies will also be screened to maximise the retrieval of relevant sources. Data will be extracted and analysed quantitatively and qualitatively, with the study procedural and reporting format following Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews guidelines.Ethics and dissemination This scoping review, through the broad and systematic mapping of existing literature, aims to provide a foundation for developing targeted support systems, strategies and interventions to address the unique needs and barriers faced by parents and caregivers of chronically ill adolescents during this critical transition to adult care.